The Impact of Gender Diversity on Firm Performance: Intellectual Capital as a Moderator - Hesniati, Hesniati; Verandi, Rizal; Yulfiswandi, Yulfiswandi (Islamic University of Kalimantan MAB Banjarmasin, 2025)
Indonesia has the highest gender gap in ASEAN. This research examines the moderating role of intellectual capital in the relationship between gender diversity and company performance. Data from industrial sector companies listed on the Indonesia Stock Exchange were analyzed using panel data and moderated regression analysis in STATA 17. A supplementary test was also conducted based on IDX board classification. Key findings include: (1) gender diversity negatively impacts firm performance; (2) structural capital weakens the negative effect of gender diversity on firm performance, while capital employed strengthens it; and (3) the positive effect of gender diversity on performance is only evident in companies listed on the main board. The study recommends future research with a broader scope, including countries that have yet to be explored. These insights highlight the complex interaction between gender diversity and intellectual capital in shaping corporate outcomes across different board classifications.